Low ATM protein expression in malignant tumor as well as cancer-associated stroma are independent prognostic factors in a retrospective study of early-stage hormone-negative breast cancer. Issue 1 (December 2015) - Feng, Xiaolan; Li, Haocheng; Dean, Michelle; Wilson, Holly; Kornaga, Elizabeth; Enwere, Emeka; Tang, Patricia; Paterson, Alexander; Lees-Miller, Susan; Magliocco, Anthony; Bebb, Gwyn
Abstract Introduction The serine/threonine protein kinase ataxia telangiectasia mutated (ATM) is critical in maintaining genomic integrity. Upon DNA double-strand breaks, ATM phosphorylates key downstream proteins including p53 and BRCA1/2, thereby orchestrating complex signaling pathways involved in cell cycle arrest, DNA repair, senescence and apoptosis. Although sporadic mutation of ATM occurs rarely in breast cancer, the status of its protein expression and its clinical significance in breast cancer remain not well established. Our study was designed to investigate the influence of ATM protein in both tumor and cancer-associated stroma on clinical outcome in hormone-positive (HPBC) and hormone-negative (HNBC) early-stage breast cancer (EBC). Methods Tissue microarrays (TMAs), containing formalin-fixed, paraffin-embedded resected tumors from two cohorts of patients (HPBC cohort: n = 130; HNBC cohort: n = 168) diagnosed at the Tom Baker Cancer Centre, Calgary, Canada, were analyzed for ATM protein expression using fluorescence immunohistochemistry (IHC) and automated quantitative analysis (AQUA). ATM expression levels were measured within the tumor as a whole (tATM) as indicated by pan-cytokeratin expression, tumor nuclear compartment (nATM) as indicated by both DAPI and pan-cytokeratin-positive results, and cancer-associated stroma (csATM) as indicated by vimentin-positive and pan-cytokeratin-negative results. ATM expression levels within these compartments were correlated with clinical outcome. Results While tATM and nATM were significantly lower in tumors compared to normal breast epithelial tissues, csATM was significantly higher than the corresponding normal tissue compartment. In addition, the median expression level of both tATM and nATM were two- to threefold lower (P <0.001) in HNBC than in HPBC. In both HNBC and HPBC cohorts, patients with low tATM, nATM and csATM tumors had significantly poorer survival outcomes than those with a high tATM, nATM and csATM, but this effect was more pronounced in HNBC. A multivariate analysis demonstrates that these biomarkers predict survival independent of tumor size and lymph node status, but only in the HNBC cohort (P <0.001). Conclusions Low ATM protein expression in both malignant tumor and stromal compartments likely contributes to the aggressive nature of breast cancer and is an independent prognostic factor associated with worse survival in HNBC patients.